Dragons in neglect: Taxonomic revision of the Sulawesi sailfin lizards of the genus Hydrosaurus Kaup, 1828 (Squamata, Agamidae) - Denzer, Wolfgang; Campbell, Patrick D.; Manthey, Ulrich; Glässer-Trobisch, Andrea; Koch, André (Zootaxa, 2020)
Currently three different species are recognized within the Southeast Asian agamid genus Hydrosaurus: H. amboinensis (Schlosser, 1768) from Ambon, Seram, Sulawesi and New Guinea, H. pustulatus (Eschscholtz, 1829) from the Philippines and H. weberi Barbour, 1911 from Halmahera and adjacent islands. Historically, two additional species were described from the island of Sulawesi, but were synonymized with H. amboinensis more than a century ago and have been treated as such in most subsequent publications. In order to revise the taxonomy and diversity of these enigmatic agamid lizards, we examined the corresponding type specimens and additional material originating from Sulawesi and compared them to photographs of live specimens from field trips. Due to differences in colour pattern and scalation characters, we resurrect the taxa celebensis Peters, 1872 and microlophus Bleeker, 1860 from the synonymy of H. amboinensis, which in turn is restricted to the central Moluccas and New Guinea. Hence, Sulawesi is currently the only known island within the genus’ range to be inhabited by two different species of sailfin lizards. Our systematic investigation brings the number of recognized species within the genus Hydrosaurus to five.